The health benefits of rooibos tea in humans (aspalathus linearis)‑a scoping review - Daniel Afrifa; Louise Engelbrecht; Bert Op't Eijnde; Elmarie Terblanche (AOSIS, 2023)
Natural remedies in the treatment of health condi‑ tions are an appealing option for many individuals. Previous studies reported that fermented and unfermented rooibos tea have considerable anti‑inflammatory and antioxidative properties. Most of this knowledge, however, originates from animal and cell culture studies. The aims of this review are to evaluate the existing, but limited, body of knowledge regarding rooibos tea interventions in humans and to iden‑ tify the gaps in the literature. The PRISMA extension for Scoping Reviews (PRISMA‑ScR) guidelines were followed in the collation of this scoping review. Among the databases searched were Google Scholar, PubMed, Cochrane Library, Scopus, and Web of Science. This review comprised 18 publications, with half (50%) of the studies being conducted in South Africa. There were 488 participants in all, ranging in age from six to 83 years, in the investigations. Rooibos tea was either fermented, unfermented, or black in 62% of the studies. Doses ranging from 200 to 1,200 ml were employed. In both healthy and at‑risk individuals, rooibos has been shown to enhance lipid profiles, boost antioxidant status, and lower blood glucose levels. The existing findings suggests that rooibos consumption demonstrated to improve lipid profiles, boost antioxidant status, and lower blood glucose levels in both apparently healthy, and individual at‑risk individuals or diagnosed of chronic conditions. Thus, it can be presumed that rooibos tea provides some health benefits, yet these findings are based on a limited number of human intervention studies and a small total sample size. Additionally, a variety of rooibos dosages and types of tea in the experiments had inconsistent results that were probably impacted by the amount consumed. Future studies should include a dose‑response study in humans, as well as large scaled clinical trials to evaluate the health effects of Rooibos.